Effects of exercise on pulmonary function tests: A comparative study between athletes and non-athletes in Nepalese settings - Mahotra, N B; Amatya, T M; Rana, B SJB; Banstola, D (Journal of Chitwan Medical College, 2017)
Due to regular exercises, athletes tend to have an increase in pulmonary functions when compared to non exercising individuals, especially when the exercise is strenuous. Intensity and severity of sports engaged in by the athletes determines the extent of strengthening of the inspiratory muscles with a resultant increase in the lung volumes and capacities. Pulmonary parameters like tidal volume and forced vital capacity are significantly higher in athletes than in non athletes. A cross sectional comparative study was carried out in national sports council, Tribhuvan army club and institute of medicine, Kathmandu, Nepal. The athletes were footballers from Tribhuvan army club and sprinters from national sports council. The non-athletes were medical students from the institute of medicine, Kathmandu. Data were collected after performing spirometry and mean values were compared between athletes and non-athletes. Pulmonary functions were assessed based on forced vital capacity (FVC), forced expiratory volume in 1 second (FEV1) and peak expiratory flow rate (PEFR) expressed as percent predicted for the age, sex, height, weight and race. Spirometry was performed in 169 subjects, out of which 84 were athletes and 85 were non-athletes. Athletes had a significantly superior FVC (P =0.00) compared to non-athletes. FEV1 was also recorded significantly higher in athletes than in non-athletes (P=0.023). Athletes have better pulmonary function tests than non-athletes because exercise in athletes strengthens the muscles of respiration.